Activation of AMP‐activated protein kinase during sepsis/inflammation improves survival by preserving cellular metabolic fitness. Issue 5 (4th April 2020) - Jin, Kui; Ma, Yujie; Manrique‐Caballero, Carlos L.; Li, Hui; Emlet, David R.; Li, Shengnan; Baty, Catherine J.; Wen, Xiaoyan; Kim‐Campbell, Nahmah; Frank, Alicia; Menchikova, Elizabeth V.; Pastor‐Soler, Nuria M.; et al.
Abstract: The purpose was to determine the role of AMPK activation in the renal metabolic response to sepsis, the development of sepsis‐induced acute kidney injury (AKI) and on survival. In a prospective experimental study, 167 10‐ to 12‐week‐old C57BL/6 mice underwent cecal ligation and puncture (CLP) and human proximal tubule epithelial cells (TEC; HK2) were exposed to inflammatory mix (IM), a combination of lipopolysaccharide (LPS) and high mobility group box 1 (HMGB1). Renal/TEC metabolic fitness was assessed by monitoring the expression of drivers of oxidative phosphorylation (OXPHOS), the rates of utilization of OXPHOS/glycolysis in response to metabolic stress, and mitochondrial function by measuring O2 consumption rates (OCR) and the membrane potential (Δψm ). Sepsis/IM resulted in AKI, increased mortality, and in renal AMPK activation 6‐24 hours after CLP/IM. Pharmacologic activation of AMPK with 5‐aminoimidazole‐4‐carboxamide ribonucleotide (AICAR) or metformin during sepsis improved the survival, while AMPK inhibition with Compound C increased mortality, impaired mitochondrial respiration, decreased OCR, and disrupted TEC metabolic fitness. AMPK‐driven protection was associated with increased Sirt 3 expression and restoration of metabolic fitness. Renal AMPK activation in response to sepsis/IM is an adaptive mechanism that protects TEC, organs, and the host by preserving mitochondrial function and metabolic fitness likely through Sirt3 signaling.